Enhancing understanding of green economy and implementing appropriate technology towards an Adiwiyata schools - Kuswati, Rini; Anggono, Agus Dwi; Syamsiyah, Nur Rahmawati; Anindita, Yessica; Zakiyah, Safira; Mahiroh, Aqila Widyas (Universitas Muhammadiyah Magelang, 2025)
In line with the focus on sustainable development, the government encourages the implementation of the green economy across various sectors, including educational institutions. This Community Partnership Empowerment Program (PKM) aims to assist SD Muhammadiyah 24 Surakarta in implementing the green economy through the Adiwiyata School initiative. The school faces several challenges, including limited green facilities, suboptimal waste management, and low environmental literacy. The PKM UMS team conducted an institutional strengthening program through socialization, workshops, and the application of technologies such as rainwater harvesting, groundwater tanks, and the design of a vertical garden with circular water. The implementation methods included socialization, training, mentoring, appropriate technology application, and evaluation. As a result, 80% of students have mastered environmental literacy, enabling them to internalize eco-friendly behaviors both at school and in their daily lives. Furthermore, support for the green economy was successfully implemented through the installation of rainwater harvesting systems, groundwater tanks, and vertical gardens utilizing circular water.